Protection from power under English law - MacDermott, John Clarke MacDermott Baron, 1896-; Hamlyn Trust (London : Stevens, 1957)
This is the age of the common man, of the ordinary citizen. But will the ordinary citizen concern himself with the amenities and frills of better living, and will he concern himself with the problem of the control of power? His liberty, and the liberty of his children, will eventually depend upon his answer to that question. The author here is concerned with those concentrations or regions of power which by their weight or their nature conduce to the oppression of the individual: the power of prosecution, the power of Parliament, the power of the executive, of wealth and of status, of monopoly and restrictive association, and the biggest problem of all, the power of numbers. How and to what extent does the law react towards power of that order? How far does it succour those upon whom such power bears? Is it the law's function to keep a fair balance between those who have and those who are subject to such power? And, if so, does the law discharge that function? In the final analysis, the common weal requires that the ordinary citizen concern himself with such questions. He must be eternally vigilant - to ensure that our law stands for what is fair and just and good.
1. Introductory -- 2. The power of prosecution -- 3. The power of Parliament -- 4. The power of the Executive -- 5. The power of wealth and the power of status -- 6. The power of monopoly and restrictive association -- 7. The power of numbers: conclusion.
"Published under the auspices of the Hamlyn Trust."
Lectures delivered at the Queen's University of Belfast, Nov. 1957.
Keywords: Civil rights -- Great Britain; Law -- Great Britain; Power (Social sciences)